2020
DOI: 10.1016/j.tipsro.2020.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting radiotherapy utilisation in geriatric oncology patients in NSW, Australia

Abstract: Background and Purpose: Large non-age-specific radiotherapy utilisation rate (RTU) studies have demonstrated that actual RTU is below the optimal recommended utilisation rate for both curative and palliative intent radiotherapy indications. The optimal utilisation rate for the geriatric oncology cohort of patients has not yet been determined. The purpose of this research was to examine the actual RTU for patients treated in New South Wales (NSW), Australia as a function of increasing age, and the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…However, the association of these factors and RTU12 varied for different cancer types. Most of the earlier studies have reported lower RTU in older patients for all cancers, 4,9,21,22 and we observed this in patients with lung cancer in our study. However, for men with prostate cancer, there was higher RTU12 in older men, similar to that reported in the NSW 45 and Up Study, 23 given that younger men were more likely to opt for surgery instead of RT for prostate cancer.…”
Section: Discussionsupporting
confidence: 83%
“…However, the association of these factors and RTU12 varied for different cancer types. Most of the earlier studies have reported lower RTU in older patients for all cancers, 4,9,21,22 and we observed this in patients with lung cancer in our study. However, for men with prostate cancer, there was higher RTU12 in older men, similar to that reported in the NSW 45 and Up Study, 23 given that younger men were more likely to opt for surgery instead of RT for prostate cancer.…”
Section: Discussionsupporting
confidence: 83%
“…Thirty studies used GIS to associate geographic measures to patient and/or health system outcomes (Table 4), such as incidence, latency for diagnosis, tumor size at diagnosis, use of primary surgery, RT utilization/interruption, delay in RURs decreased with increasing distances to nearest RT centers. This was demonstrated for palliative RT, 40,51 adjuvant RT for breast cancer, 3,4,34,35,39,45,46,[49][50][51]59,60 rectal cancer, 4,22,40,49,60,61 lung cancer, 4,22,34,40,49,51,60 colon cancer, 47,49 and prostate cancer. 22,49,60 Regional differences were noted in Norway, Australia, the United Kingdom, and the United States.…”
Section: Gis Used To Analyze Health Systems or Patient Outcomesmentioning
confidence: 91%
“…This was demonstrated for palliative RT, 40,51 adjuvant RT for breast cancer, 3,4,34,35,39,45,46,[49][50][51]59,60 rectal cancer, 4,22,40,49,60,61 lung cancer, 4,22,34,40,49,51,60 colon cancer, 47,49 and prostate cancer. 22,49,60 Regional differences were noted in Norway, Australia, the United Kingdom, and the United States. 3,34,40,50,56,62,63 Other covariates such as sex, 22,34,38,40,47,49,51,61 age, 3,22,34,35,…”
Section: Gis Used To Analyze Health Systems or Patient Outcomesmentioning
confidence: 91%
“…So, for example, early prostate cancer rates will always be affected by the availability of surgery, what options and toxicities the urologists discuss with their patients prior to (if at all) a radiotherapy appointment pre‐surgery and whether a consultation takes place 13,14 . While attempts are being made to refine our models using data on age, frailty and co‐morbidity, there are also studies showing that older patients with good life expectancy are still missing out on radiotherapy 15 …”
mentioning
confidence: 99%
“…13,14 While attempts are being made to refine our models using data on age, frailty and co-morbidity, there are also studies showing that older patients with good life expectancy are still missing out on radiotherapy. 15 Where patients are missing out on more significant treatment benefits identified from clinical trials, this should remain a major cause for concern. For example, Ong et al in this current report show that approximately 1 in 5 patients with Stage 3 breast cancer did not receive radiotherapy.…”
mentioning
confidence: 99%